2021
DOI: 10.1108/ijoem-05-2021-0810
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the impact of artificial intelligence on the competitiveness of tourism firms: a modified total interpretive structural modeling (m-TISM) approach

Abstract: PurposeThis study explores the variables that drive the impact of artificial intelligence (AI) on the competitiveness of a tourism firm. The relationship between the variables is established using the modified total interpretive structural modelling (m-TISM) methodology. The factors are identified through literature review and expert opinion. This study investigates the hierarchical relationship between these variables.Design/methodology/approachThe modified total interpretive structural modelling (m-TISM) met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 75 publications
(128 reference statements)
0
11
0
2
Order By: Relevance
“…Future researchers are also encouraged to use m-TISM as a simpler and more convenient way of constructing structural explanatory models to validate their results and findings if there are fewer variables, the field of study is well established and the relevant literature is extensive. [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93]…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Future researchers are also encouraged to use m-TISM as a simpler and more convenient way of constructing structural explanatory models to validate their results and findings if there are fewer variables, the field of study is well established and the relevant literature is extensive. [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93]…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Still, Rajan et al (2021) suggested a study to analyze the strategic management of cybersecurity in an organization, and other analyses applied the m‐TISM analysis to model sustainability factors in the healthcare industry (Sindhwani et al, 2022). Finally, the m‐TISM was used to explore the effect of artificial intelligence on firms' competitiveness, focusing on the tourism sector (Sharma et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…AI-based systems – such as chatbots and virtual assistants – are changing the tourism and hospitality industry. Using a modified total interpretive structural modeling approach, Sharma et al (2022) explored the factors influencing tourism firms' overall performance. Hierarchical interrelationships among these factors are crucial to realizing AI's potential.…”
Section: Articles In the Special Issuementioning
confidence: 99%
“…In “Analysing the impact of artificial intelligence on the competitiveness of tourism firms: A modified total interpretive structural modeling (m-TISM) approach,” Sharma et al (2022) focus on tourism firms' use of AI to boost their competitiveness. Researchers and practitioners are optimistic that AI can help tourism firms profitably deliver services and products at competitive prices while enhancing customers' satisfaction.…”
Section: Articles In the Special Issuementioning
confidence: 99%